Stroke prevention. MATCHing therapy to the patient with TIA. - Weir, N; Demchuk, A; Buchan, A; Hill, MD (2005)
The short-term risk of stroke after transient ischemic attack (TIA) is about 10% to 20% in the first 3 months, with much of the risk front-loaded in the first week. Unfortunately, little is known about the best therapies for hyperacute stroke prevention after TIA. A recent trial referred to by the acronym MATCH (for Management of Atherothrombosis With Clopidogrel in High-risk Patients With Recent Transient Ischemic Attack or Ischemic Stroke) provides hypothesis-generating data to suggest that double antiplatelet therapy in the short term may be appropriate. Here, the authors discuss treatment considerations, outlining the current knowledge and stressing the need for formal randomized trials to definitively establish the effectiveness of preventive therapies after minor stroke or TIA.